Neurological Symptom Improvement After Re-Irradiation in Patients With Diffuse Intrinsic Pontine Glioma: A Retrospective Analysis of the SIOP-E-HGG/DIPG Project - Chavaz, Lara; Janssens, Geert O.; Bolle, Stephanie; Mandeville, Henry; Ramos-Albiac, Monica; Van Beek, Karen; Benghiat, Helen; Hoeben, Bianca; Morales La Madrid, Andres; Seidel, Clemens; Kortmann, Rolf-Dieter; Hargrave, Darren; et al. (Frontiers in Oncology, 2022)
Purpose The aim of this study is to investigate the spectrum of neurological triad improvement in patients with diffuse intrinsic pontine glioma (DIPG) treated by re-irradiation (re-RT) at first progression. Methods We carried out a re-analysis of the SIOP-E retrospective DIPG cohort by investigating the clinical benefits after re-RT with a focus on the neurological triad (cranial nerve deficits, ataxia, and long tract signs). Patients were categorized as “responding” or “non-responding” to re-RT. To assess the interdependence between patients’ characteristics and clinical benefits, we used a chi-square or Fisher’s exact test. Survival according to clinical response to re-RT was calculated by the Kaplan–Meier method. Results As earlier reported, 77% (n = 24/31) of patients had any clinical benefit after re-RT. Among 25/31 well-documented patients, 44% (n = 11/25) had improvement in cranial nerve palsies, 40% (n = 10/25) had improvement in long-tract signs, and 44% (11/25) had improvement in cerebellar signs. Clinical benefits were observed in at least 1, 2, or 3 out of 3 symptoms of the DIPG triad, in 64%, 40%, and 24%, respectively. Patients irradiated with a dose ≥20 Gy versus <20 Gy may improve slightly better with regard to ataxia (67% versus 23%; p-value = 0.028). The survival from the start of re-RT to death was not different between responding and non-responding DIPG patients (p-value = 0.871). Conclusion A median re-irradiation dose of 20 Gy provides a neurological benefit in two-thirds of patients with an improvement of at least one symptom of the triad. DIPG patients receiving ≥20 Gy appear to improve slightly better with regard to ataxia; however, we need more data to determine whether dose escalation up to 30 Gy provides additional benefits.